Improving Mouse Controlling and Movement for People with Parkinson’s Disease and Involuntary Tremor Using Adaptive Path Smoothing Technique via B-Spline. - Bani hashem, Seyed Yashar; Mat Zin, Nor Azan; Mohd Yatim, Noor Faezah; Mohamed Ibrahim, Norlinah (Assistive Technology)
Many input devices are available for interacting with computers, but the computer mouse is still the most popular device for interaction. People who suffer from involuntary tremor have difficulty using the mouse in the normal way. The target participants of this research were individuals who suffer from Parkinson’s disease. Tremor in limbs makes accurate mouse movements impossible or difficult without any assistive technologies to help. This study explores a new assistive technique—adaptive path smoothing via B-spline (APSS)—to enhance mouse controlling based on user’s tremor level and type. APSS usesMeanfiltering and B-spline to provide a smoothed mouse trajectory. Seven participants who have unwanted tremor evaluated APSS. Results show that APSS is very promising and greatly increases their control of the computer mouse. Result of user acceptance test also shows that user perceived APSS as easy to use. They also believe it to be a useful tool and intend to use it once it is available. Future studies could explore the possibility of integrating APSS with one assistive pointing technique, such as the Bubble cursor or the Sticky target technique, to provide an all in one solution for motor disabled users.